2012
DOI: 10.1073/pnas.1120916109
|View full text |Cite
|
Sign up to set email alerts
|

MtPAR MYB transcription factor acts as an on switch for proanthocyanidin biosynthesis in Medicago truncatula

Abstract: MtPAR (Medicago truncatula proanthocyanidin regulator) is an MYB family transcription factor that functions as a key regulator of proanthocyanidin (PA) biosynthesis in the model legume Medicago truncatula. MtPAR expression is confined to the seed coat, the site of PA accumulation. Loss-of-function par mutants contained substantially less PA in the seed coat than the wild type, whereas levels of anthocyanin and other specialized metabolites were normal in the mutants. In contrast, massive accumulation of PAs oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
156
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 140 publications
(159 citation statements)
references
References 40 publications
(37 reference statements)
3
156
0
Order By: Relevance
“…and alfalfa, consistent with our result that MtMYB14 is able to promote PA accumulation in M. truncatula hairy roots. MtPAR, another TT2-related MYB transcription factor in M. truncatula, also promotes PA accumulation in M. truncatula hairy roots and alfalfa plants (Verdier et al, 2012). PA accumulation is also induced by strong expression of Arabidopsis TT2 in M. truncatula hairy roots (Pang et al, 2008).…”
Section: Myb5 and Myb14 Physically Interact And Synergisticallymentioning
confidence: 99%
See 3 more Smart Citations
“…and alfalfa, consistent with our result that MtMYB14 is able to promote PA accumulation in M. truncatula hairy roots. MtPAR, another TT2-related MYB transcription factor in M. truncatula, also promotes PA accumulation in M. truncatula hairy roots and alfalfa plants (Verdier et al, 2012). PA accumulation is also induced by strong expression of Arabidopsis TT2 in M. truncatula hairy roots (Pang et al, 2008).…”
Section: Myb5 and Myb14 Physically Interact And Synergisticallymentioning
confidence: 99%
“…Recently, we discovered that another M. truncatula MYB transcription factor, PAR, also regulates PA biosynthesis in the M. truncatula seed coat (Verdier et al, 2012). Unlike loss of function of MYB5 and MYB14, the par mutant exhibits a lighter seed coat color than the wild type, indicating that PAR either regulates both anthocyanin and PA biosynthesis or does not negatively regulate the anthocyanin pathway.…”
Section: Downstream Targets Of Myb5 and Myb14 In M Truncatulamentioning
confidence: 99%
See 2 more Smart Citations
“…Stracke et al (2007) found that AtMYB11/PFG1, AtMYB12/PFG1 and AtMYB111/PFG3 controled flavones biosynthesis in all tissues while AtMYB75/ PAP1, AtMYB90/PAP2, AtMYB113 and AtMYB114 regulated anthocyanin biosynthesis in vegetative tissues (Gonzalez et al 2008) while AtMYB123/TT2 controlled the biosynthesis of proanthocyanidins (PAs) in the seed coat of Arabidopsis (Lepiniec et al 2006). Verdier et al (2012). Found that MtPAR (Medicago truncatula proanthocyanidin regulator) was a MYB family transcription factor that functioned as a key regulator of proanthocyanidin (PA) biosynthesis in the model legume Medicago truncatula and could be of great potential for biotechnological strategies to increase PAs in forage legumes for reduction of pasture bloat in ruminant animals.…”
Section: Regulation Of Primary and Secondary Metabolismmentioning
confidence: 99%